Carbon Footprint and Sustainability in The Operating Room: What to Know on the Road to Becoming a Green Operating Room - Ezgi Seyhan Ak; Öykü Kara (Lokman Hekim Dergisi, 2025)
The biggest threat to global health in the 21st century is climate change. Greenhouse gas emissions, one of the biggest causes of climate change, originate 4 to 10% from healthcare services. These emissions cause negative environmental impacts by increasing the carbon footprint. Operating rooms, with their large share in energy and resource consumption, make the biggest contribution to the increase in carbon footprint in healthcare services. Transforming operating rooms into green operating rooms that adopt and implement measures against climate change significantly contributes to maintaining and improving global health, protecting natural resources, and ensuring sustainability. In order to reduce emissions from operating rooms, reusable products should replace single-use products, medical and surgical gas usage should be reduced, and the right anesthesia and sterilization methods should be selected. In addition, reducing the length of hospital stay, waste and energy consumption, and digitalizing documentation and communication are additional measures to lower emissions. In reducing the carbon footprint and ensuring sustainability, it is crucial that these practices are understood and adopted by the operating room team and that green operating rooms are created. This study aims to examine the carbon footprint in the operating room in line with the literature, practices, and sustainability to reduce the carbon footprint and to convey what needs to be known on the way to becoming a green operating room.